Verrucous epidermal nevus. - Garofalo, L. (European Journal of Pediatric Dermatology, 2010)
Verrucous epidermal nevus is a clonal proliferation of mutated keratinocytes (2), due to a post-zygotic mutation occurred during the fetal life, and thus expression of cutaneous mosaicism affecting one of the numerous genes involved in the morphogenesis of keratinized epithelia (1). This explains why it is clinically characterized by a linear distribution and why thickening of the epidermis is highly variable ranging from non palpable hyperpigmentation, usually visible in some initial lesions, to a more or less raised verrucous lesion, that can be clinically and histologicaly reminiscent of common wart, condylomata acuminate, seborrheic keratosis, acanthosis nigricans or incontinentia pigmenti.